American Consumer’s Attitudes towards Different Airline Companies Channels: A Comparison of transaction Methods - Talha Harcar; Ugur Yucelt (PASOS Revista de Turismo y Patrimonio Cultural, 2012)
Consumers are increasingly challenging better performance from companies, and these demands are being met through improvements in technology and flexibility of services. As a result of recent progresses and developments in electronic marketing, the physical locations of brick and mortar businesses have become less significant since transactions can now be accomplished in cyberspace. In this paper, consumer attitudes towards online transactions for the airline industry are examined. Despite the growing acceptance of alternative delivery channels, the travel agencies remain an essential part of the customer-airline company. It can be argued that the travel agencies not only represent an opportunity for implementing costumer relationship, but they also remain an important point of contact for sales, service, and consultative interactions. Data has been analyzed using factor analysis technique. The study presents a broad picture of the level of preference of airline customers among the available distribution channels and sheds light on how airline companies should allocate resources among the different channels. The empirical study findings indicate that online transactions for the airline industry will gain in importance and its use will accelerate at a faster rate in the coming years.